A new species and a new record of Peliosanthes (Asparagaceae) from eastern Thailand - Tanaka, Noriyuki; Kalyuzhny, Sergey S. S. (Phytotaxa, 2020)
Peliosanthes oksanae is described and illustrated as a new species from eastern Thailand. It is most similar to P. gracilipes known from northern and southwestern Thailand and northwestern Laos, from which it differs mainly by the shorter flowering stem, flowers borne singly or binately in the axils of the bracts and almost free oblong filaments not forming a typical corona. We briefly discuss taxonomic relationships between P. oksanae and two similar species, P. gracilipes and P. caesia. It is notable that especially P. oksanae and P. gracilipes are close in floral characters to Ophiopogon. We also report P. triandra, which was described from southern Cambodia, as new to Thailand. Both P. triandra and P. oksanae occurred in the same habitat.